Mechanical and durability properties of steel, polypropylene and polyamide fiber reinforced slag-based alkali-activated concrete - Kuranli, Omer Faruk; Uysal, Mucteba; Abbas, Mele Tidjani; Cosgun, Turgay; Nis, Anil; Aygormez, Yurdakul; Canpolat, Orhan; Al-mashhadani, Mukhallad M. (TAYLOR & FRANCIS LTD, 2023)
Alkali-activated composites are significant materials in reducing CO2 emissions and ensuring sustainability. With the increasing concerns about climate change globally, the interest in alkali-activated materials has also increased. Researching different fibers has very important potential in this area. This study aims to make alkali-activated concretes widespread in the concrete sector by using the materials common in conventional concretes and ensuring that alkali-activated concretes are an alternative in terms of sustainability. Experimental studies were conducted to examine the mechanical, durability, and microstructural properties (SEM) of slag-based alkali-activated concrete (AASC) reinforced with three various fibers. The fibers, polypropylene (PP), polyamide (PA), and steel (ST), were used with two ratios (%0.4 and %0.8 by vol.). Compressive, splitting tensile, and flexural strength tests were carried out at 28 and 90 days. In terms of durability properties, the samples were exposed to high temperatures (300-600-900 degrees C) and freeze-thaw test (250 cycles). The results showed that the addition of fibers improved the strength and durability properties; for instance, the existence of steel and polypropylene fibers increased the flexural toughness factor values by 430% and 260%, respectively. Moreover, the compressive strength of the fibrous samples exposed to 900 degrees C was obtained in the range of 6-23 MPa.
Keywords: GGBS; alkali-activated concrete; steel fiber; synthetic fibers; high-temperature; freeze-thaw; HIGH-TEMPERATURE BEHAVIOR; GEOPOLYMER CONCRETE; FLEXURAL BEHAVIOR; PERFORMANCE; RESISTANCE; Engineering